2020
DOI: 10.3390/ijms21041245
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Ficus carica Peels with a Focus on the Key Genes for Anthocyanin Biosynthesis

Abstract: Fig (Ficus carica L.), a deciduous fruit tree of the Moraceae, provides ingredients for human health such as anthocyanins. However, little information is available on its molecular structure. In this study, the fig peels in the yellow (Y) and red (R) stages were used for transcriptomic analyses. Comparing the R with the Y stage, we obtained 6224 differentially expressed genes, specifically, anthocyanin-related genes including five CHS, three CHI, three DFR, three ANS, two UFGT and seven R2R3-MYB genes. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 81 publications
1
24
0
Order By: Relevance
“…In addition to bHLH-2, bHLH-1 proteins could act in controlling anthocyanin biosynthesis . bHLH-1 and bHLH-2 transcription factors are suggested to function via distinct mechanisms (Pesch et al, 2015;.A previous transcriptome study has revealed that FcMYB114, FcCPC, FcMYB21, and FcMYB123 might regulate anthocyanin biosynthesis in the fig fruit (Wang et al, 2019;Li et al, 2020a). WD40 and other MYB transcription factors are shown to be positively correlated with FcbHLH42 in this study, which provides the basis for better analyses of various regulatory models of anthocyanin synthesis in figs.…”
Section: Fcbhlh Involvement In Fig Fruit Anthocyanin Biosynthesissupporting
confidence: 57%
See 1 more Smart Citation
“…In addition to bHLH-2, bHLH-1 proteins could act in controlling anthocyanin biosynthesis . bHLH-1 and bHLH-2 transcription factors are suggested to function via distinct mechanisms (Pesch et al, 2015;.A previous transcriptome study has revealed that FcMYB114, FcCPC, FcMYB21, and FcMYB123 might regulate anthocyanin biosynthesis in the fig fruit (Wang et al, 2019;Li et al, 2020a). WD40 and other MYB transcription factors are shown to be positively correlated with FcbHLH42 in this study, which provides the basis for better analyses of various regulatory models of anthocyanin synthesis in figs.…”
Section: Fcbhlh Involvement In Fig Fruit Anthocyanin Biosynthesissupporting
confidence: 57%
“…The co-expression of VvMYC1 and VvMYBA1 in grape suspension cells led to anthocyanin accumulation (Hichri et al, 2011a). Previous transcriptome analysis of fig has suggested that FcMYB114, FcCPC, FcMYB21, and FcMYB123 regulate anthocyanin biosynthesis (Wang et al, 2019;Li et al, 2020a), but that no anthocyanin-related fig bHLH has been identified. In addition, genes from bHLH subgroup III d + e have been shown to regulate the jasmonic acid (JA) signaling pathway, thereby enhancing plant defense capabilities and promoting anthocyanin biosynthesis (Xie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The MYB transcription factors, which belong to one of the largest and most diverse transcription factor families in the plant kingdom, are common among eukaryotes and play essential roles in diverse physiological and biochemical processes controlling plant growth and development [ 46 , 47 ]. The bHLH transcription factors, which possess a highly conserved bHLH domain that includes a basic region and an HLH region, are crucial for plant growth and development, metabolic regulation, and responses to environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…The MYB transcription factors, which belong to one of the largest and most diverse transcription factor families in the plant kingdom, are common among eukaryotes and play essential roles in diverse physiological and biochemical processes controlling plant growth and development [49,50]. The bHLH transcription factors, which possess a highly conserved bHLH domain that includes a basic region and an HLH region, are crucial for plant growth and development, metabolic regulation, and responses to environmental changes.…”
Section: Discussionmentioning
confidence: 99%